Isl1 is required for multiple aspects of motor neuron development - Liang, Xingqun (2011)
The LIM homeodomain transcription factor Islet1 (Isl1) is expressed in multiple organs and plays essential roles during embryogenesis. Isl1 is required for the survival and specification of spinal cord motor neurons. Due to early embryonic lethality and loss of motor neurons, the role of Isl1 in other aspects of motor neuron development remains unclear. In this study, we generated Isl1 mutant mouse lines expressing graded doses of Isl1. Our study has revealed essential roles of Isl1 in multiple aspects of motor neuron development, including motor neuron cell body localization, motor column formation and axon growth. In addition, Isl1 is required for survival of cranial ganglia neurons.